Effect of Rutin on Gentamicin-Induced Ototoxicity in Rats: A Biochemical and Histopathological Examination - Salcan, İsmail; Dilber, Muhammet; Bayram, Rana; Süleyman, Esma; Naz Yazıcı, Gülce; Çoban, Abdulkadir; Süleyman, Halis (ENT Updates, 2021)
Objective: Gentamicin is a broad-spectrum aminoglycoside antibiotic administered parenterally for moderate to severe gram-negative infections. Ototoxicity is an important side effect that limits gentamicin use. The aim of this study is to investigate the effect of rutin on gentamicin-induced ototoxicity in rats biochemically and histopathologically. Methods: Distilled water was administered by oral gavage to healthy controls (HG) and cobalt administered group (GC). 50 mg/kg rutin was administered by oral gavage to rutin + gentamicin (RGG) group. After one hour, 100 mg/kg gentamicin was injected intraperitoneally (i.p) to the RGG and GC animal groups. This procedure was repeated once a day for 14 days. Results: Malondialdehyde (MDA), nuclear factor-κB(NF-κB), tumor necrosis factor alpha (TNF-α) and interleukin-1 beta(IL-1β) levels in the cochlear nerve tissue of gentamicin-treated animals were significantly higher compared to healthy controls and rutin + gentamicin treated rats. On the other hand, the amount of total Glutathione (tGSH) was significantly lower compared to the control and rutin group. Histopathological examination revealed degenerated myelinated nerve fibers in the gentamicin group and Schwann cell nuclei were generally not seen. There was a high accumulation of collagen fiber in the tissue and dilated blood capillaries. In the rutin group, myelinated nerve fibers mostly exhibited normal morphology, Schwann cell nuclei were evident and the vessels were normal. Conclusion: Our experimental results suggest that rutin may be effective in the treatment of gentamicin-associated ototoxicity.